Inhibition of MMP14 potentiates the therapeutic effect of temozolomide and radiation in gliomas. (30th June 2013) - Ulasov, Ilya; Thaci, Bart; Sarvaiya, Purvaba; Yi, Ruiyang; Guo, Donna; Auffinger, Brenda; Pytel, Peter; Zhang, Lingjiao; Kim, Chung Kwon; Borovjagin, Anton; Dey, Mahua; Han, Yu; et al.
Abstract Metalloproteinases are membrane‐bound proteins that play a role in the cellular responses to antiglioma therapy. Previously, it has been shown that treatment of glioma cells with temozolomide (TMZ) and radiation (XRT) induces the expression of metalloproteinase 14 (MMP14). To investigate the role of MMP14 in gliomagenesis, we used several chemical inhibitors which affect MMP14 expression. Of all the inhibitors tested, we found that Marimastat not only inhibits the expression of MMP14 in U87 and U251 glioma cells, but also induces cell cycle arrest. To determine the relationship between MMP14 inhibition and alteration of the cell cycle, we used an RNAi technique. Genetic knockdown of MMP14 in U87 and U251 glioma cells induced G2/M arrest and decreased proliferation. Mechanistically, we show that TMZ and XRT regulated expression of MMP14 in clinical samples and in vitro models through downregulation of microRNA374. In vivo genetic knockdown of MMP14 significantly decreased tumor growth of glioma xenografts and improved survival of glioma‐bearing mice. Moreover, the combination of MMP14 silencing with TMZ and XRT significantly improved the survival of glioma‐bearing mice compared to a single modality treatment group. Therefore, we show that the inhibition of MMP14 sensitizes tumor cells to TMZ and XRT and could be used as a future strategy for antiglioma therapy.